2023
DOI: 10.5114/ceh.2023.130605
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the efficiency and safety of anticoagulation therapy in patients with liver cirrhosis and atrial fibrillation

Alina Baylo,
Volodymyr Cherniavskyi,
Dmytro Reshotko

Abstract: Aim of the study Currently, there are insufficient scientific data regarding the efficacy and safety of direct oral anticoagulants (DOACs) compared to warfarin in patients with both liver cirrhosis (LC) and atrial fibrillation (AF). The aim of the study was to analyze the frequency and risk factors for the development of thrombotic and hemorrhagic complications in patients with LC and AF after DOAC treatment compared to warfarin. Material and methods A randomized clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…There was no evidence of significant heterogeneity (I-square: 0%). References [12][13][14][15][16][17][18][19]21].…”
Section: Safety Outcome (Major Bleeding Events)mentioning
confidence: 99%
See 3 more Smart Citations
“…There was no evidence of significant heterogeneity (I-square: 0%). References [12][13][14][15][16][17][18][19]21].…”
Section: Safety Outcome (Major Bleeding Events)mentioning
confidence: 99%
“…Despite this, DOACs have gained traction and are now recommended in the BAVENO guideline for patients with Child-Turcotte-Pugh (CTP) A and B cirrhosis [11]. Different studies have compared DOACs in patients with liver cirrhosis [12][13][14][15][16][17][18][19][20][21]. However, much of the evidence supporting the use of DOACs in atrial fibrillation patients with liver cirrhosis has primarily come from studies with small sample sizes [12,13,15,17,18].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, a recent small RCT of moderate quality involving 56 patients with CTP-A and CTP-B cirrhosis and atrial fibrillation has shown a significantly lower overall frequency of bleeding events with dabigatran compared to VKA. 106 The choice of anticoagulation in patients with CTP-C cirrhosis remains an open question because only limited data are available on the subject. Small-scale observational studies of fewer than 20 patients with CTP-C cirrhosis found no statistical difference in efficacy and safety between DOAC and traditional anticoagulants for treating VTE and preventing systemic embolism in case of atrial fibrillation.…”
Section: Direct Oral Anticoagulants and Cirrhosismentioning
confidence: 99%